2019
DOI: 10.1186/s13046-019-1473-8
|View full text |Cite
|
Sign up to set email alerts
|

Exosomal lncRNA ZFAS1 regulates esophageal squamous cell carcinoma cell proliferation, invasion, migration and apoptosis via microRNA-124/STAT3 axis

Abstract: BackgroundIn recent years, long non-coding RNAs (lncRNAs) are of great importance in development of different types of tumors, while the function of lncRNA ZFAS1 is rarely discussed in esophageal squamous cell carcinoma (ESCC). Therefore, we performed this study to explore the expression of exosomal lncRNA ZFAS1 and its molecular mechanism on ESCC progression.MethodsExpression of ZFAS1 and miR-124 in ESCC tissues was detected. LncRNA ZFAS1 was silenced to detect its function in the biological functions of ESCC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
107
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 148 publications
(121 citation statements)
references
References 27 publications
1
107
1
Order By: Relevance
“…In this study, we confirmed that USP5 mediated STAT3 signaling. The signal transducer and activator of transcription 3 (STAT3) is an important signaling mediator, which plays significant roles in a vast array of biological processes 26 - 28 . It has been confirmed that overexpression or overactivation of STAT3 is required for tumorigenesis and metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we confirmed that USP5 mediated STAT3 signaling. The signal transducer and activator of transcription 3 (STAT3) is an important signaling mediator, which plays significant roles in a vast array of biological processes 26 - 28 . It has been confirmed that overexpression or overactivation of STAT3 is required for tumorigenesis and metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, MSCs-derived exosomes have gradually attracted our attention 16,17 . Especially, exosomes could transmit lncRNAs to cancer cells and therefore accelerate the progression of multiple cancers 18,19 . In the present study, we discovered that LINC01559 was upregulated in GC tissues and could be transmitted from MSCs to GC cells by exosomes.…”
Section: Introductionmentioning
confidence: 99%
“…Increasing studies have demonstrated that lncRNAs might act as tumor oncogenes in the initiation and progression of human cancers, and several lncRNAs may even become novel biomarkers in cancer. For example, lncRNA ZFAS1 might be a poor prognostic factor and promote tumor progression, including non-small cell lung cancer and esophageal squamous cell carcinoma [17,18]. However, the roles and underlying mechanisms of lncRNAs in GBM remain unknown.…”
Section: Discussionmentioning
confidence: 99%